P-27 OBESITY AND LIVER STEATOSIS IN ADOLESCENTS AND YOUNG ADULTS - RELATED FACTORS AND THE IMPACT OF LIFESTYLE - Fabiana Martins Basilio; Ana Carolina Cardoso; Katia Bloch; Nathalie Leite; Cristiane Villela-Nogueira (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Obesity and lifestyle are factors associated with steatotic liver disease related to metabolic dysfunction (MASLD). Objective: To describe the frequency of obesity and MASLD in adolescents/young adults and related factors. Patients / Materials and Methods: Cross-sectional study. Demographic, anthropometric and lifestyle data were assessed (self-completed questionnaire). All underwent liver elastography with CAP (Fibroscan® Touch 502, Echosens, Fr) to estimate the frequency of steatosis (CAP ≥ 248 DB/m) and significant fibrosis (E > 7.9 kPa). The related factors for obesity and steatosis were assessed by logistic regression analysis. Results and Discussion: One hundred and twenty-three healthy individuals participated in the study (68.3% women, 19.5 ± 1.5 years). Pre-hypertension, overweight and obesity were identified in 13.3%, 16.3% and 10.6% respectively (62.8% were not satisfied with their weight). Alcohol consumption was 26.7% (2-4 drinks/week), higher in men. 6% had glycated hemoglobin ≥ 5.7% (Pre-diabetes) and 28% had hypercholesterolemia. Steatosis was identified in 21.1%, and no individual had significant fibrosis [median E = 4.4 (3.6 – 5.3) kPa]. The median daily time spent on the computer was 5 (3-8 hours), and 56% used the computer for more than 4 hours/day. The factors that were independently associated with obesity in these adolescents were pre-hypertension (OR 8.7: 95% CI 2.1-36.0, p=0.003) and time spent using a computer (OR 6.1: 1.09-34.9; p=0.039). Obesity (OR 71.4: 95%CI 7.0-725.5, p<0.001), pre-hypertension (OR 7.4: 95%CI 1.3-41.9, p=0.024) and male sex (OR 13.5: 95%CI 1.3-137.3, p=0.027) but not alcohol use was associated with the presence of hepatic steatosis. Conclusions: The prevalence of obesity, pre-hypertension and hepatic steatosis in adolescents/young adults is high. Lifestyle changes, including better control of screen time, must be implemented urgently in this population to combat obesity and steatosis.